INNOVATIVE MECHANISMS OF THE DEVELOPMENT OF LOCAL DEMOCRACY: EFFICIENCY, CONDITIONS OF USE, PERSPECTIVES - HONYUKOVA, Liliya; DERUN, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article aims to investigate the conditions, expediency and foreign practice of using innovative mechanisms for the development of local democracy. Based on the generalization of the scientific works of Ukrainian and foreign scientists, the necessity of using a comprehensive approach to strengthening democracy at the local level was determined. It is noted that the decentralization reform needs to be deepened by developing a set of mechanisms that will enable democratization processes to be activated at the local level. The role of local democracy in the development of a democratic system is revealed. It was emphasized that the local government should see citizens as its partners with whom it cooperates. Accordingly, the local government should be interested in improving the forms of interaction with the community through the development of effective mechanisms. The article presents an overview of the constitutional conditions for the use of innovative mechanisms, outlines the list of criteria for evaluating democratic innovations, in particular: inclusiveness, popular control, weighted decisions, transparency. Obstacles to the strengthening of democracy, which remain and need to be leveled at the expense of finding effective mechanisms, are analyzed. Examples of individual countries and cities that are leaders in the use of innovative mechanisms for the development of local democracy are given. The practice of using such mechanisms in Ukraine as local referendums, general meetings of citizens, local initiatives and public hearings, local (public) initiatives has been analyzed. Measures are proposed, the implementation of which will ensure the activation of the use of innovative mechanisms for the development of local democracy.